The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/21645515.2022.2049168
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden in patients with severe hand, foot, and mouth disease in Jiangsu Province: a cross-sectional study

Abstract: This study aimed to estimate the disease burden and health-related quality of life (HRQOL) among patients with severe hand, foot, and mouth disease (HFMD) in Jiangsu Province, China. We analyzed the surveillance data of HFMD cases in Jiangsu Province from 2009 to 2020. Moreover, a cross-sectional study was conducted in Nanjing and Suzhou, China, between January 2017 and May 2018. Patients with severe HFMD and their parents were recruited from selected hospitals. Questionnaires and hospital management systems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Several studies have explored the economic burden of HFMD patients in China [ 4 , 10 12 , 20 ]. Compared with the studies that included inpatients with worse conditions [ 4 , 10 , 20 ], in our study, lower average hospitalization and total costs were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the economic burden of HFMD patients in China [ 4 , 10 12 , 20 ]. Compared with the studies that included inpatients with worse conditions [ 4 , 10 , 20 ], in our study, lower average hospitalization and total costs were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The three-level EuroQol-five dimensions (EQ-5D-3L) proxy 2 questionnaire [ 9 ] and TNO-AZL Preschool Quality of Life (TAPQOL) scale [ 10 ] were used to assess the health-related quality of life (HRQOL) of pediatric patients with HFMD. The results suggested that HFMD impaired the patients’ health in terms of both psychological and physical aspects [ 9 , 10 ], and thus reduced their HRQOL. However, few studies have used child-specific HRQOL instruments and compared health status changes before and after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current rate of EV-A71 vaccination still needed to be promoted, and Han et al. revealed that the overall vaccination rate for children in the birth cohort reached 19.63–28.63% from 2016 to 2019 in Jiangsu Province [ 36 ]. Although there is currently no licensed CV-A16 vaccine for use in humans, Sun et al.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 and has been used to measure HRQoL in different pathologies, on occasions not specifying the psychometric properties of those populations. 10,13,[21][22][23][24][25][26][27] Given that the reliability and validity are not intrinsic properties of questionnaires, but depend on the target population of the measure, the purpose of this study was the psychometric assessment of the TAPQOL questionnaire in patients with CAO that guarantees the results when applied to this population. The statistics used, Cronbach's α for the reliability analysis, and principal component analysis for the validity are endorsed by the bibliography.…”
Section: Discussionmentioning
confidence: 99%